Analisis Penjadwalan Produksi dengan Metode Campbell Dudek Smith untuk Meminimasi Makespan pada PT.XYZ - Rohmah, Safiur; Saifuddin, Joumil Aidil; Prameswari, Mega Cattleya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT. XYZ is a wood-made furniture manufacturing company, one of which is a chair with a variety of types like arm chair, a bar drum, a drum counter and side chair. In the process, sometimes some orders are late. It's in the high-solution total time. Therefore, scheduling in the company requires a renewal of methods to identify which methods of scheduling efficiency in reducing production. Campbell dudek Smith's method is used because control processes are done according to the smallest working time used in production. Campbell dudek Smith's methods are appropriate and can be applied to help control the production with a flower-shop system that is more than two machines. Results from research obtained a large schedule at company scheduling FCFS method of 9613425 seconds with job sequence 1-2-3-4. While the Campbell dudek Smith method obtained a period of 9608298 seconds with the job sequence 2-3-1-4. The Campbell dudek Smith method was chosen as a proposal because it had the smallest byline of corporate methods.